PENGARUH MOTIVASI TERHADAP KINERJA PEGAWAI DINAS KEHUTANAN DAN PERKEBUNAN KABUPATEN DONGGALA - Firman, Mohamad (Katalogis, 2015)
The purpose of this research is to determine and analyze the effect of motivation on employees’ performance of Forestry and Plantation Agency of district Donggala. This is a quantitative research using survey approach. The population of this research is the employees of the Forestry and Plantation Agency of District Donggala totaling 83 people that were drawn using Taro Yamane’s formulation and then it is determined that the number of samples are 45 respondents by using stratified random sampling technique because of the stratified characteristics of the population. Data collection method consists of observation, questionnaires and documentation, while data analysis techniques used is simple linear regression. The result shows that there is an influence of motivation on employees’ performance of Forestry and Plantation Agency of District Donggala, where the influence of the motivation is controlled by the dimensions of the need for power, especially in the case of employees having desire to get power or responsibility in completing their works, while the low dimension is the need for achievement, which means that employees are not motivated to achieve work result personally.